2020
DOI: 10.1098/rsbl.2020.0580
|View full text |Cite
|
Sign up to set email alerts
|

Energetic mechanisms for coping with changes in resource availability

Abstract: Given current anthropogenic alterations to many ecosystems and communities, it is becoming increasingly important to consider whether and how organisms can cope with changing resources. Metabolic rate, because it represents the rate of energy expenditure, may play a key role in mediating the link between resource conditions and performance and thereby how well organisms can persist in the face of environmental change. Here, we focus on the role that energy metabolism plays in determining organismal responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…The timing of maturation, just as many life-history traits, depends on reaching a certain body size threshold, i.e., the acquisition of sufficient energy that can be allocated for maturation processes (Moghadam et al 2007;Taranger et al 2010;Verta et al 2020). Because of context-dependent covariation between metabolism and growth rate (see meta-analysis by Auer et al (2020b)), we tested if resource availability modified the genetic covariation between metabolic phenotypes and age-at-maturity. Against our predictions, our experiments did not reveal a change in SMR or MMR, or genotype-by-environment interactions, due to feed restriction, despite a strong decrease in growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of maturation, just as many life-history traits, depends on reaching a certain body size threshold, i.e., the acquisition of sufficient energy that can be allocated for maturation processes (Moghadam et al 2007;Taranger et al 2010;Verta et al 2020). Because of context-dependent covariation between metabolism and growth rate (see meta-analysis by Auer et al (2020b)), we tested if resource availability modified the genetic covariation between metabolic phenotypes and age-at-maturity. Against our predictions, our experiments did not reveal a change in SMR or MMR, or genotype-by-environment interactions, due to feed restriction, despite a strong decrease in growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Vgll3 genotype has been shown to have a strong effect on salmon life-history (Ayllon et al, 2015;Barson et al, 2015;Verta et al, 2020), and recent findings have suggested that this effect might be mediated by vgll3-induced differences in body condition (Debes et al, 2021). Taking this together with the connections between standard metabolic rate (SMR) and resource acquisition and assimilation (Armstrong et al, 2011;Auer, Bassar, et al, 2020;Auer, Solowey, et al, 2020;Bochdansky et al, 2005;Millidine et al, 2009;Rosenfeld et al, 2015), we hypothesized that vgll3 genotype might be asserting some of its effects through changes in energetic physiology that would be reflected in SMR. However, we did not detect any difference in either SMR or body condition between juvenile Atlantic salmon individuals of different homozygous vgll3 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic phenotype is a multi-faceted set of traits, covering not just standard metabolic rate, but also the maximum metabolic rate, aerobic scope, and daily energy expenditure, to mention some. Additionally, the consequences of variation in metabolic traits are context-dependent and may change under different environmental conditions and life stages (Auer, Bassar, et al, 2020;Auer, Solowey, et al, 2020;Bochdansky et al, 2005;Millidine et al, 2009;Norin & Metcalfe, 2019). We initially planned to also measure metabolic rate under exhaustive swimming to obtain data on maximum metabolic rate (MMR), but had to abandon these trials as we were unable to motivate juvenile salmon of this age and size to do any exhaustive swimming, either by swim tunnel or by hand chasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased population density and the resulting change in food availability could influence the expression of phenotypic traits in three separate, non-exclusive ways (Auer et al 2020). First, by reducing per-capita food availability, they may lead to plastic changes in resource-dependent traits.…”
Section: Introductionmentioning
confidence: 99%